Validation of predictive equations of the cross-sectional area of the human trunk. 10.5007/1980-0037.2011v13n6p461 - Jorge Estrela Morais; Mário Jorge Costa; Jean Erik Mejias; Daniel Almeida Marinho; António José Silva; Tiago Manuel Barbosa (Universidade Federal de Santa Catarina, 2011)
The objective of this study was to develop and validate predictive equations of the cross-sectional area of the human trunk. The models were developed for males according to their level of expertise. The sample comprised 152 male subjects, all of them with a background in competitive or recreational swimming. Their ages ranged between 10 and 32 years. Two different groups of subjects were used to estimate and validate the equation. The following anthropometric characteristics were assessed: (i) body weight, (ii) height, (iii) biacromial diameter, (iv) sagittal thoracic diameter, (v) chest circumference, and (vi) cross-sectional area of the trunk. Predictive models were developed using stepwise multiple linear regression analysis. One of the models used level of expertise as a dummy variable. All models included sagittal thoracic diameter and chest circumference as independent variables (0.32 ≤ R2 ≤ 0.48; P < 0.01). The validation process of the measured and estimated cross-sectional area of the trunk did not reveal any significant differences between the mean values (P > 0.05). The simple linear regressions were moderate (0.23 ≤ R2 ≤ 0.55; 0.01 ≤ P ≤ 0.001), and the Bland-Altman criterion was met in all cases. Therefore, our findings suggest that the models developed for male swimmers according to their level of expertise are able to provide a valid prediction of the cross-sectional area of the trunk.